Socio-economic status and feeding practices among the mothers of under-five children in an urban slum of Bangladesh: a cross-sectional study - Amin, AFM Sujauddoula Al; Debnath, Sumon Chandra; Galib, Asadullahil; Rouf, Md Abdur; Haque, Md Ekramul; Rabby, Md Fazlay; Zannat, Taslima; Rahim, Zahidur (Asian Journal of Medical and Biological Research, 2018)
Poor socio-economic conditions and inappropriate feeding practices in slum dwelling mothers can have adverse consequences for the health and nutritional status of their under-five children. The present study was to assess the feeding practices and socio-economic status mothers of under-five children. A cross-sectional study was conducted from January 2015 to December 2015 in four urban slums of Bangladesh. Two hundred and fifty five mother-child pairs were selected by non-random convenience sampling and were interviewed using a pre-tested questionnaire. Anthropometric measurements were taken from under-five children aged 6-59 months. In the present study, boys (54.0%) were predominant over girls (46.0%). The prevalence of initiation of breastfeeding after delivery, prelacteal feeds, exclusive breastfeeding and bottle-feeding were 34.5%, 43.5%, 39.6% and 30.6%, respectively. Out of 255 children studied, more than half (57.6%) of the children received complementary feeds at the appropriate time whereas 45.9% children received with appropriate consistency. Meal frequency was 40.4% and minimum dietary diversity was given to only 39.6% of the children. Minimum dietary diversity means feeding the child food from at least four food groups. Feeding practices improve as mother‟s education levels and household income status increases while maximum slum dwelling mothers are illiterate and primary level completed and household income status are not static. Data showed that overall 14.0% of under-five children were suffering from malnutrition. In terms of severity, 11.3% were moderately malnourished-MAM and 2.7% were severely malnourished-SAM. Various inappropriate feeding practices are more prevalent among urban slum mothers. From this study, it was evident that mothers of low socio-economic group have poor knowledge regarding the feeding practices of their under-five children. There is an urgent need to bridge the “knowledge gap” and “practice gap” of mother‟s from urban slum and lower socio economic strata of the community by further strengthening the on-going breastfeeding programme, breastfeeding knowledge and practice of mothers in urban slum areas. Asian J. Med. Biol. Res. September 2018, 4(3): 307-314